Consistency between 3 days' dietary records and 24-h urine in estimating salt intake in children and adolescents - Dong, Jie; Yu, Xiaoran; Li, Xun; Xiang, Shiting; Qin, Yongquan; Zhu, Shaolun; Zheng, Jie; Yan, Yinkun (Frontiers in Public Health, 2022)
Purpose: This study aimed to estimate the level of salt intake by three-consecutive-days’ collection of 24-h urine and weighed diets in young students, and to compare the differences between the two methods. Methods: This was a school-based cross-sectional study. The overweight (including obesity) or the hypertensive students aged 6-14 years, and their normal counterparts, were recruited into this study in three boarding schools in China. Twenty-four-hour urine in three-consecutive-weekdays were collected from all the participants. During the same period, the weighed diets were recorded in children who have all three meals at the school canteens during weekdays. Incomplete 24-h urine or dietary records were excluded in analysis. Results: The median salt excretion was 6218 [4636, 8290] mg by 24-h urine and 120 (82.2%) consumed excess salt in all the participants. The median salt intake was 8132 [6348, 9370] mg by dietary records and 112 (97.4%) participants consumed excess salt than recommended in participants who have all three meals in the school canteens. In children who both had dietary records and 24-h urine, the level of salt intake estimated by 24-h urine accounted for 79.6% of the dietary records. Conclusion: There were significant discrepancies between dietary records and 24-h urine in estimating salt intake in children and adolescents. And the weighed dietary record was recommended if feasible. Policies or strategies targeted at school canteens are warranted to reduce the salt intake of the young generation.